This can be made more student-centred: Asynchronous mediation in in-service teacher professional development - Victoria Kareva; Tatiana Rasskazova; Dmitri Leontjev (Peoples' Friendship University of Russia (RUDN University), 2022)
Vygotskian Sociocultural Theory is a powerful foundation for research into teacher professional development. However, while this research has been growing, it has largely been focused on pre-service second/foreign language. Furthermore, there is a lack of research on how the instructional process informed by the principles of Sociocultural Theory, including assessment of candidates' mediated performance, can be orchestrated to promote teachers' conceptual development and induce changes in their classroom practices. The present study explores how asynchronous assessment of in-service teachers' portfolios (with the focus on lesson planning) informed by dynamic assessment framework shaped the tutor's mediation in synchronous online interaction with two teacher candidates. Theoretically, the study was informed by Vygotskian notion of true concepts. Focusing on two candidates in the training, we traced their trajectories regarding their conceptual development and the development of their practices. We will namely, illustrate how the information received in assessment guided the tutor's mediation, and how the synchronous interactions in the course shaped and helped to interpret the assessment of candidates' unassisted and mediated performance on portfolios. We will discuss implications of our study and will argue for shifting the focus beyond single classroom activities in Sociocultural Theory research.